(untitled) (PKP Barcelona 2019 Workshop, 2019)
As Journal Manager go to Settings > Website > Plugins • Core OJS: Pre-installed plugins • Plugin Gallery: Additional community plugins Useful plugins: • Tracking site visits: Google Analytics | Piwik/Matomo • Social media article usage: addThis | Plum analytics • Single Sign-on: Shibboleth | SubscriptionSSO • Custom content: Static Pages | Custom Blocks • Article viewers: • PDF.JS PDF Viewer | HTML Article Galley | XML Lens Article Viewer • Indexing: OAI | Dublin Core | Google Scholar • Upload articles ready for publication : QuickSubmit • Anti-spam: Google reCaptcha | Honeypot | Akismet • Plagiarism detection: iThenticate